Persepsi Pasien Geriatri tentang Kualitas Pelayanan Kesehatan di Rumah Sakit X di Kabupaten - Rizki Fitriani, Atmim; Rondhianto, Rondhianto; Hamzah, Zahreni (LPPM Hang Tuah Pekanbaru, 2025)
Background: The increasing number of elderly people in Indonesia demands improvements in health services. Elderly individuals, with their vulnerability to diseases, require quality services that meet their expectations. This study describes how elderly patients evaluate the quality of services they receive at Hospital X in Jember Regency. Method: This study uses a descriptive quantitative approach with a survey method to collect data. A total of 269 patients participated in this study, selected through a simple random sampling process. A modified SERVQUAL questionnaire was used to measure patient perceptions. The data obtained were analyzed using the SPSS application. Results: The perception of geriatric patients assessed the quality of service at Hospital X in Jember Regency in the high category (96.3%) which included the dimensions of physical evidence (97%), reliability (94.8%), responsiveness (94.4%), assurance dimension (98.5%), empathy (99.3%) and accessibility and affordability (91.8%). Conclusion: Positive perceptions of geriatric patients are an indicator of a hospital's success in providing quality healthcare services that meet the standards for elderly patients.